(untitled) (Current Horticulture, 2024)
The field experiments were conducted to develop fertilizer best management practice (FBMP) by site specific nutrient management (SSNM) and SSNM zonation maps and customised fertilizer ratios at ICAR-CTCRI, Thiruvananthapuram, Kerala, India, during 2012-2015. The SSNM plot resulted in an average actual tuberous root yield of 36.80, 37.40 and 38.70 t/ha during 2012, 2013 and 2014 respectively against a yield target of 40 t/ha. The average yield difference between SSNM and PR for the three crops grown was 5.50 t/ha (17%, P=0.001) and was similar during all the three years. On an average, plant N accumulation increased by 48 kg/ha (25%, P=0.003), P accumulation by 9 kg/ha (50%, P=0.003), and K accumulation by 39 kg/ha (20%, P=0.005). Among the three crops grown, the AEN increased by 34 kg/kg (72%, P=0.002), REN by 0.04 kg/kg (8%, P=0.003) and PEN by 55 kg/kg (58%, P=0.005). The guidelines in estimating the fertilizer N, P2O5 and K2O required by cassava based on tuberous root yield response to fertilizer N, P and K and efficiency of fertilizer N, P and K use also were developed. Soil fertility maps and agro-ecological units, SSNM zonation maps and customised fertilizer ratios were also developed for all the major cassava-growing regions in India.